Proceso de evaluación psicopedagógica para determinar las necesidades específicas de apoyo educativo en un estudiante con síndrome de Klinefelter (variante 49 XXXXY) de séptimo grado de la escuela municipal de educación básica Capulí Loma, 2023. - Ortiz Cumbicus, Robin Jairo (2025)
The present curricular integration work focused its objective on analyzing the psychopedagogical evaluation process to determine the specific needs of educational support in an atypical case with Klinefelter syndrome (variant 49 XXXXY) a seventh grade student at the Capulí Loma School, 2023, to describe what the psychopedagogical evaluation process consists of in a case study, taking into account the aforementioned, interviews were conducted with the teacher and the mother of the family. For this purpose, a qualitative study was carried out, of a descriptive non- experimental scope, semi-structured interviews were conducted, based on the criteria of those involved and the theory, building an analysis through a deductive process . From the results obtained it is worth highlighting that according to the perceptions of the teacher and the mother of the family, the student faces multiple difficulties in his learning process, highlighting problems in oral expression, confusion with letters, poor comprehension when reading, limitations in mathematics and difficulties in writing, lack of motivation, constant accompaniment to avoid distraction and frustration, in personal autonomy, in the emotional field, it is observed that the student expresses frustration and sadness at not understanding instructions, and finally the need for greater communication and collaboration between the family and the school. It is determined that the specific needs for educational support presented by the student with KS, are evaluated in: language ( Peabody test ), with an IQ of 55. In psychomotor skills ( Tepsi ), there is a risk in coordination skills; and, a significantly low performance in motor skills. In reading and writing ( Baneta Test ) there is a low to average level; in addition, a low cognitive profile is observed in attention, memory and comprehension, phonological processing and grammar. In mathematics (Precalculus Test), he has basic notions to perform addition, subtraction. In basic functions (Bat 7 Test), he presents a low performance in various areas of cognitive aptitude with verbal and spatial difficulties, problems retaining visual images. His attention is poor, he has low processing speed and difficulties maintaining concentration. In learning style (Learning Channel Preference Test), he demonstrates a low visual style. In social interaction, (EHS), he presents significant difficulties. Regarding the psychopedagogical evaluation report, it contains aspects that take into account the areas evaluated, where a developmental delay is observed in almost all areas and at the same time some guidelines are written for 5 psychopedagogical support from school and at home for the mother of the family. In conclusion, according to everything commented on the perceptions of the teacher and the mother of the family, the student faces multiple difficulties in his learning process, in almost all areas and with specific needs for educational support evaluated as a result of the integration of personal characteristics in the case of KS, to which those from the syndrome can be associated, such as certain difficulties with language, motor skills, basic functions, mathematics, attention deficit and difficulty in social relationships, manifesting mainly in a greater difficulty for learning. Hence, the particular limitations in mobility, communication, language or in social interaction and development, become needs to which educational, personal and social responses must be given, within the educational community with a vision of psychopedagogical and social support. In this way, the development of psychopedagogical orientations or methodological guidelines for educational and social intervention by the teaching team and family, with the intention of functional and community integration, achieves a social value, focusing these interventions on the development of their capacities, reducing the diagnosis resulting from the psychopedagogical evaluation and promoting the personal and social acceptance and integration of the student with KS.